Speed and Income - Fosgerau, Mogens (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
The average speed on Danish motorways has been increasing for a number of years. In this paper we seek to provide at least a partial explanation for this development. First we establish in a micro-economic model how higher income can lead to a higher choice of speed. With increasing income, the value of time increases and the costs of driving faster decrease in importance, both operating costs and potential fines. Second, we utilize a cross-section dataset comprising 60.000 observations of car trips to perform a regression of speed on income, distance traveled and a number of controls. The results indicate a clear relationship between speed and income whereby a 100.000 kroner increase in pretax income, about 35 percent of the average income in the sample, is associated with a speed increase of 2 km/h at longer distances.